Strategi Pembelajaran Kooperatif Terhadap Peningkatan Karakter Religius Siswa dalam Mata Pelajaran PAI - Nurlaila Ramadhani; Nisa Adriani; Gusmaneli Gusmaneli (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study aims to explore how cooperative learning strategies contribute to the enhancement of students’ religious character within the context of Islamic Religious Education (PAI). Using a literature review approach, this research collects and analyzes various scholarly sources concerning cooperative learning models, religious character values, and the teacher’s role in shaping students' personalities based on Islamic principles. The findings indicate that cooperative learning strategies not only engage students cognitively but also create a learning environment that fosters the internalization of religious values such as honesty, responsibility, discipline, empathy, and tolerance. The teacher's role as a facilitator is crucial in guiding group dynamics to be infused with moral and spiritual values. Thus, this strategy proves to be both relevant and effective in supporting a holistic approach to religious character education.